Protocol for visualizing the chromatin assembly properties of epigenetic protein complexes via an HTM module-mediated artificial tethering system - Shanli Guan; Jiajia Tang; Cuixia Di; Bo Cheng (STAR Protocols)
Summary: The detailed chromatin assembly processes for many epigenetic regulatory complexes are largely unknown. Here, we present a protocol utilizing heterochromatin-targeting module (HTM) module-mediated chromatin tethering followed by microscopy-based visualization to detect the recruitment priority between two components in Polycomb repressive complex 1 (PRC1). Moreover, we detail procedures for detecting the resultant histone-modifying activities of PRC1 using immunofluorescence (IF) analyses. This approach allows directly visualization of the on-chromatin assembly of the histone-modifying complexes of interest in live cells.For complete details on the use and execution of this protocol, please refer to Cheng et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.